Acoustic Emission Response and Damage Process for Q235 Steel in an in Situ Tensile Test - ZHANG, Ying; LI, Yue; LAI, Huan Sheng; BAI, Chunmei; LIU, Kang Lin (Archives of Acoustics, 2019)
Q235 steel is widely used in engineering and construction. Therefore, it is important to identify the damage mechanism and the acoustic emission (AE) response of the material to ensure the safety of structures. In this study, an AE monitor system and an in situ tensile test with an optical microscope were used to investigate the AE response and insight into the damage process of Q235 steel. The surface of the specimen was polished and etched before the test in order to improve the quality of micrographs. Two kinds of AE responses, namely a burst and a continuous signal, were recorded by the AE monitor system during the test. Based on the in situ test, it was observed that the damage of Q235 steel was induced by the crystal slip and the inclusion fracture. Since the crystal slip was an ongoing process, continuous AE signals were produced, while burst AE signals were possibly produced by the inclusion fracture which occurred suddenly with released higher energy. In addition, a great number of AE signals with high amplitude were observed during the yielding stage and then the number and amplitude decreased.